2010
DOI: 10.2322/tastj.8.9
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Approach using Plasma Jets to Realize the Radicals' Effects for Improving Ignition and Combustion

Abstract: To introduce an alternative fuel to a combustion system or develop a more sophisticated system used in aeronautical and other engineering fields, the combustion characteristics of the fuel must be fully understood. Therefore, some effects of radical species, which are involved and play a significant role in the combustion process, must be understood to arrive at a new technology, such as for super-lean combustion or low-quality fuel utilization, which in turn would lead to solutions for recent energy issues. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…and nitrogen plasma jets (N 2 P.J.) were conducted in order to compare the effectiveness of oxygen atoms and nitrogen atoms in DME-air mixture combustion; spectroscopic measurements in a previous paper 6) reported the presence of O and N atoms in O 2 P.J. and N 2 P.J., respectively.…”
Section: Effect Of Feedstock Typementioning
confidence: 99%
See 1 more Smart Citation
“…and nitrogen plasma jets (N 2 P.J.) were conducted in order to compare the effectiveness of oxygen atoms and nitrogen atoms in DME-air mixture combustion; spectroscopic measurements in a previous paper 6) reported the presence of O and N atoms in O 2 P.J. and N 2 P.J., respectively.…”
Section: Effect Of Feedstock Typementioning
confidence: 99%
“…In a previous report, 6) we showed that the proposed approach was appropriate for evaluating and comparing the effectiveness of each radical species in terms of ignition limits and combustion completeness for dimethyl ether (DME), CH 3 OCH 3 , a promising next-generation alternative fuel, 7) as a test trial case under some conditions.…”
Section: Introductionmentioning
confidence: 99%